AGE-RELATED ULTRASOUND MORPHOMETRY OF HUMAN PROSTATE ORGANOMETRIC PARAMETERS AND ITS CHANGES IN CHRONIC ALCOHOLISM - Radjabov A.B. (Western European Studies, 2024)
The article presents the results of a study on age-related ultrasound morphometry of the biometric parameters of the human prostate and its changes during chronic alcohol exposure. Age-related changes in the prostate are uneven, which is due to the morphofunctional characteristics of the organ in different age periods. The greatest increase in prostate length was revealed in adolescence (34.0%), in adolescence the thickness increases by 38.5%, the width by 2.0 times, the volume of the gland by 3.4 times. The smallest increase in the volumelinear parameters of the gland was found in men of senile age. In men suffering from chronic alcoholism, there is an increase in the organometric parameters of the prostate gland
Keywords: prostate; postnatal ontogenesis; organometric parameters